Pertumbuhan Tanaman Duku Belum Menghasilkan terhadap Aplikasi Pupuk Kompos Kotoran Kambing dan Pupuk NPK - Gusniwati Gusniwati; Elis Kartika; Lizawati Lizawati (Agric, 2025)
Duku production and productivity in Jambi Province remain low because the existing plants are old, and cultivation technology is not precise. Efforts to overcome this problem include rejuvenation using superior seeds obtained through propagation of shoot grafting. Intensification can be done through fertilization. One fertilizer option is goat manure compost combined with NPK. The purpose of this research is to develop a technology package to accelerate duku growth in ultisols. This research was conducted in the Faculty of Agriculture’s experimental garden for 4 months on 1-year-old duku plants. The design used in this study was a randomized block design (RAK) with one factor, namely the dose of goat compost fertilizer consisting of five levels, namely 100% NPK (306g); 5 kg Goat Compost + 75% NPK (229.5g); 10 kg Goat Compost + 50% NPK Fertilizer (153g); 15 kg Goat Compost + 25% NPK (76.5g); 20 kg Goat Compost Fertilizer. Observations were made on the variables of increase in plant height, increase in stem diameter, increase in the number of leaf tillers, bud break time, and increase in the number of branches. The results showed that goat compost combined with NPK can substitute for NPK fertilizer. The application of 15 kg of goat manure compost with 25% NPK content showed the best combination for supporting the growth of immature Duku plants.